Anaesthesia provision, infrastructure and resources in the Heilongjiang Province, China: a cross-sectional observational study - Jian Zhang; Hui Wang; Fei Han; Ge Jiang; Xi Zhang; Guonian Wang; Xiaoyu Zheng; Jingshun Zhao; Dandan Yao; Wanchao Yang; Xuesong Ma; Xiaodi Lu; et al. (BMJ Open)
Objective The aim of this study was to explore the current status of the anaesthesia provision, infrastructure and resources in the Heilongjiang Province, China.Design A cross-sectional observational study of hospitals, anaesthesiologists, assistant anaesthesiologists and anaesthetic nurses in the Heilongjiang Province.Setting All hospitals in the Heilongjiang Province.Participants The hospitals, anaesthesiologists (attending physicians, associate chief physicians and chief physicians), assistant anaesthesiologists (licenced assistant physicians, resident physicians and other trainees) and anaesthetic nurses.Main outcome measures Standard descriptive statistics (percentages and numbers) were used to summarise the data.Results The investigation involved 1123 hospitals, 405 of these hospitals had anaesthesiology departments (36.06%). There were 2406 anaesthesiologists, 175 assistant anaesthesiologists and 409 anaesthetic nurses. The proportion of anaesthesiologists was 56.60% in tertiary hospitals, 40.15% in secondary hospitals and 3.25% in primary hospitals and ungraded hospitals, respectively. Anaesthesiologists were present in 91.20% of public hospitals and 8.80% of private hospitals. Anaesthesiologists were present in 83.55% general hospitals and 16.45% of specialised hospitals. The Heilongjiang Province has a total of 2041 operating rooms and 543 beds in recovery rooms. The number of anaesthesia cases per capita per year was 326.86. The percentages of anaesthesiologists’ age ≥46, 36–45, 25–35 and <25 are 24.03%, 41.80%, 33.91% and 0.27%, respectively. The proportions of resident physicians and attending physicians were 60.87%, and the proportions of associate chief physicians and chief physicians were 39.13%. The proportions of anaesthesiologists working >12 hours, 10 hours≤time≤12 hours, 8 hours≤time<10 hours and <8 hours were 0.55%, 22.04%, 64.30% and 13.11%, respectively.Conclusions The present study demonstrated for the first time that the proportion of anaesthesiologists in the Heilongjiang Province, China, is still insufficient. The structure of anaesthesiologists needs to be optimised.